Pemodelan dan Simulasi Proses Adsorpsi Gas Pengotor oleh Molecular Sieve pada Pendingin Rde dengan Software Chemcad - Sriyono, Sriyono; Hilda, Atiqah M.; Kamayani, Mia (Prosiding Seminar Nasional Teknoka, 2018)
The purity of RDE10 helium coolant should be maintained from various impurities gas due to water/air ingress that reacts with the reflector graphite (C). These impurities are CH4, CO, CO2, H2O, H2, O2, and N2 which can initiate oxidation corrosion or carburization-decarburization so the concentration should be maintain to be a minimum. The helium coolant is purified by Helium Purification System (HPS). One of the stages in HPS is adsorption by Molecular Sieve mainly for CO2 and H2O molecules. This paper discusses the influence of pressure, known as pressure swing adsorption (PSA) on the adsorption ability of the Molecular Sieve aims to determine the most effective pressure that will be operated on Molecular Sieve column. Molecular Sieve is modeled with CHEMCAD computer code in two columns, one column for the adsorption process, and the other for the regeneration (desorption). Adsorption methods used in the analysis is the Langmuir method. Models that have been developed simulated by providing input: total flow rate of 10.5 kg/hour, 30 °C, porosity 0.7, bed height 2 m, pore diameter 5 A, and the amount of O2 and N2 impurities respective each 1 g/s. The pressure varies between 5 to 50 bars, and the Molecular Sieve adsorption capability is analyzed. Simulation results show that with the increase in pressure of 5 to 50 bar, indicating an increase in Molecular Sieve absorption capacity to CO2 is 15.90% and to H2O is 15.80%. In the SPH design, the input stream to the Molecular Sieve must be compressed until 50 bar to obtain high absorption capability of the CO2 and H2O.